A study of tooth brushing pattern and its effects on dental tissues in Obafemi Awolowo University students - E.E. Akhimie; F.O. Oginni; A.O. Oginni (Nigerian Dental Journal)
Objective: To determine the tooth brushing patterns among Obafemi Awolowo University (OAU) students and the effects on dental tissues. Method: A convenient sampling technique was used to select 100 undergraduate students of the Obafemi Awolowo University. A self administered questionnaire designed to determine respondents' demographics and tooth brushing techniques was employed. Thereafter, dental examination was carried out on all respondents. Data was inputted and subjected to computer analysis using the Statistical package for social science version 17.0 (SPSS). Result: Majority (95%) of the respondents used toothbrush in cleaning their teeth while 7% combined toothbrush and chewing stick. Ninety nine percent of the respondents used toothpaste in cleaning their teeth, 72.7% of the respondents brushed their teeth once a day and 24.2% brushed twice a day. Fifty two percent of the respondents who brushed twice a day were females, while 48% were males. The pattern of tooth brushing was correct in 51.7% of the respondents as reported. Use of highly abrasive agents was also rare. Gingival recession was found in 31% of subjects (p=0.15) that employed hard texture toothbrush. The prevalence of non carious cervical lesion was 3% and these lesions were found in males only. Conclusion: The pattern of tooth brushing was correct in 51.7% of the respondents as reported. However the effect on dental tissues though present is not exaggerated when compared to other studies done in other parts of the  world.